(3QSGdI aj aQGFV GdhVhA hSffgs - (3CMeO Hf fGUQs
(3ChdgG (B:s
(3GdMeO ddg MeOG WjHG YWQ Ke GdUdGI Ydi GdeNJGQ ef eVQG (B- (3eMeO NjQ Ndb Gddg cdge hBdg hYdi CUMGHg GdcHQGs
(3BNQgG (B:s
(3Ke eHjJ efi hGdLeY aj YQaG J hGdOYGA haj LeY EPG faQG (B- (3heTYQ hLeGQ hGdMdGb hJQ c GdWjH hGdUjO aGbJUQG (B- (3bO GfJgi hdQH GdMeO CLeYg Ke GdSdGe Ydi GdeNJGQ ef eVQGs
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdbWQjIs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
Keywords: (3Gdabg GdMfHdjs